El Caso. An historical-journalistic approach to a Spanish events weekly publication - Rodríguez Cárcela, Rosa María (2012)
The article is an historical and journalistic study about El Caso, an events weekly newspaper, which was published during 40 years in Spain. We analyze the historic evolution of this publication, from Franco’s dictatorship to the coming of the democracy, as well as its style and its striking covers. This newspaper was one of the most successful in Spain over the 20th century, was a remarkable example of profitable popular press, and its director, Eugenio Suárez, created one of the first Spanish Media groups.